REDUCING INSECURITY THROUGH CLASSICAL GUIDANCE SERVICES WITH GAME BASED LEARNING METHOD AND CARD GAME MEDIA - Wardhani, Dardaniela Yosi; Dwikurnaningsih, Yari (Jurnal Bikotetik (Bimbingan dan Konseling: Teori dan Praktik), 2024)
Based on the preliminary study at SMP Negeri Salatiga, it was found that the level of self-confidence was in the low criteria, in this case one aspect of self-confidence is insecurity. This study aims to reduce insecurity in students through classical guidance services with game-based learning methods and game card media. This research uses mixed methods or a combination of quantitative and qualitative methods with a sequential explanatory model, which begins with quantitative data collection as a general description of the level of insecurity and is strengthened by qualitative data as further explanation through observations and interviews. The subjects in this study used all students in class VIII F SMP Negeri Salatiga who became the target class in conducting classical guidance. Based on quantitative results, it is known that the classical guidance model is proven to reduce insecurity in students. This is indicated by a change in the decrease before (pre-test) and after (post-test) given services of 15.7%. The output significance result = 0.00 < 5%, so it means that the pre-test average is different from the post-test average. Reinforced by observations and interviews which show that the condition of students has been able to accept themselves and be able to encourage themselves to appear when presenting in front of the class. So that the classical guidance model with the game-based learning method and game card media can be used as an alternative in reducing insecurity in students.